The One Nutrition in Complex Environments (ONCE) study protocol: a cluster-randomized multi-level multi-sectoral intervention to improve nutrition in Uganda - Griswold, Stacy P.; Marshak, Anastasia; Fitzpatrick, Merry; Lantagne, Daniele; Shoenmakers, Kate; Hebie, Marlene; Radday, Anne; Groote, Hugo de; Mehta, Saurabh; Gottlieb, Greg; Webb, Patrick; Ghosh, Shibani (Springer, 2022)
Objective: To implement and measure the effects of a multi-level multi-sectoral social behavior change (SBC) intervention in Agago District of Northern Uganda and to determine the potential for scale-up. Intervention: Compare the Nutrition Impact and Positive Practice (NIPP) approach to a NIPP+ approach. The NIPP approach involves nutrition education and SBC, whereas the NIPP+ adds agricultural inputs, training, and tools to support improved farm and water quality practices. The intervention effect will be measured through lower levels of aflatoxin in grain, lower water contamination, and improved knowledge on nutrition and health. Design: This is a three-arm cluster-randomized controlled superiority trial (cRCT). The study arms include the following: group 1: NIPP; group 2: NIPP+, and group 3: control. Groups 1 and 2 will receive a 12-week intervention (NIPP or NIPP+) with active monitoring and longitudinal follow-up at 2, 6, and 12 months post-intervention. Additionally, an in-depth process and performance evaluation of each intervention arm will be undertaken using quantitative and qualitative methods. A total of 60 clusters from 5 subcounties of the Agago district will be randomly selected, and 15 households per cluster will be recruited using specific inclusion/exclusion criteria for a total of 900 households (300/arm). Respondents for the qualitative portion will be purposely selected. Analysis: We will collect data from all participants at 3 time points: baseline, endline, and 12 months post-intervention. The analysis will utilize intent-to-treat (ITT) using the initial randomization of the treatment arms to determine the overall impact of having the NIPP vs. NIPP+ vs. control. Mixed effects models will be used to determine the role of time-variant and invariant individual household, and community characteristics, as well as measures of exposure and integration on key outcome indicators. A difference-in-difference analysis (baseline/endline, baseline/12 months post-intervention, endline/12 months post-intervention) will also be used to triangulate findings.